2017
DOI: 10.1038/s41598-017-09306-x
|View full text |Cite
|
Sign up to set email alerts
|

Small molecules enhance CRISPR/Cas9-mediated homology-directed genome editing in primary cells

Abstract: CRISPR/Cas9 is an efficient customizable nuclease to generate double-strand breaks (DSBs) in the genome. This process results in knockout of the targeted gene or knock-in of a specific DNA fragment at the targeted locus in the genome of various species. However, efficiency of knock-in mediated by homology-directed repair (HDR) pathway is substantially lower compared with the efficiency of knockout mediated by the nonhomologous end-joining (NHEJ) pathway. Suppressing NHEJ pathway or enhancing HDR pathway has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 25 publications
4
103
1
Order By: Relevance
“…The The distribution of efficiencies is shown in Figure 1, clearly demonstrating the 3-fold lower efficiency for HDR (median = 0.199) compared to NHEJ (median = 0.606) when choosing targets traditionally. These values are comparable to previous work (21)(22)(23).…”
Section: A Dataset Of Genome-wide Hdr Efficienciessupporting
confidence: 92%
“…The The distribution of efficiencies is shown in Figure 1, clearly demonstrating the 3-fold lower efficiency for HDR (median = 0.199) compared to NHEJ (median = 0.606) when choosing targets traditionally. These values are comparable to previous work (21)(22)(23).…”
Section: A Dataset Of Genome-wide Hdr Efficienciessupporting
confidence: 92%
“…At this stage, genetic knockouts are facile, but replacing sequences by HDR remains inefficient and technically challenging, although great strides are being made to improve the technique. [65][66][67][68][69][70][71][72] CRISPR systems have generated an extraordinary level of excitement for the clinical potential for curing human disease. In this nascent stage of CRISPR in the clinic, initial applications are treating diseases with the most accessible cells (immune cells and HSPCs edited ex vivo), which avoids the ongoing challenge of tissue-specific delivery in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…65 The likelihood of successful insertion can be improved using a few different strategies, but the general inefficiency of this gene replacement approach represents a substantial challenge in the field. [65][66][67][68][69][70][71][72] As our ability to carefully manipulate DNA grows, so will the clinical potential of CRISPR technologies. 17 CURRENT AND NEAR-TERM THERAPEUTIC APPLICATIONS Genetic therapies offer hope for treating and effectively curing monogenic diseases by reversing the underlying genetic cause.…”
Section: Repurposing Crispr Proteins For Genome Editingmentioning
confidence: 99%
“…While these studies showed promising results in improving CRISPR/Cas9 activity, it was recently reported that successful knock‐in in mouse ES cells and zygotes using the targeted insertion of large DNA fragments (7.4 kb and 5.8 kb) was achieved without any NHEJ inhibitors . Also, HDR can be facilitated with greater target specificity by using a Cas9 mutant Cas9n that can cleave only a single DNA strand; and that the CRISPR/Cas9‐mediated HDR can be enhanced by adding small molecules, such as resveratrol, Scr7, and L755507 . Addition of these molecules to the cell culture medium boosted HDR efficiency two‐ to three‐fold in porcine fetal fibroblast cells after they were transfected with the homologous template DNA and a CRISPR/Cas9 plasmid.…”
Section: Challenges For Crispr/cas9 Gene Editingmentioning
confidence: 99%